Quantitative and qualitative estimation of atherosclerotic plaque burden in vivo at 7T MRI using Gadospin F in comparison to en face preparation evaluated in ApoE KO mice. - Caroline Jung; Sabine Christiansen; Michael Gerhard Kaul; Eva Koziolek; Rudolph Reimer; Jörg Heeren; Gerhard Adam; Markus Heine; Harald Ittrich (PLoS ONE)
Background The aim of the study was to quantify atherosclerotic plaque burden by volumetric assessment and T1 relaxivity measurement at 7T MRI using Gadospin F (GDF) in comparison to en face based measurements. Methods and results 9-weeks old ApoE-/- (n = 5 for each group) and wildtype mice (n = 5) were set on high fat diet (HFD). Progression group received MRI at 9, 13, 17 and 21 weeks after HFD initiation. Regression group was reswitched to chow diet (CD) after 13 weeks HFD and monitored with MRI for 12 weeks. MRI was performed before and two hours after iv injection of GDF (100 μmol/kg) at 7T (Clinscan, Bruker) acquiring a 3D inversion recovery gradient echo sequence and T1 Mapping using Saturation Recovery sequences. Subsequently, aortas were prepared for en face analysis using confocal microscopy. Total plaque volume (TPV) and T1 relaxivity were estimated using ImageJ (V. 1.44p, NIH, USA). 2D and 3D en face analysis showed a strong and exponential increase of plaque burden over time, while plaque burden in regression group was less pronounced. Correspondent in vivo MRI measurements revealed a more linear increase of TPV and T1 relaxivity for regression group. A significant correlation was observed between 2D and 3D en face analysis (r = 0.79; p<0.001) as well as between 2D / 3D en face analysis and MRI (r = 0.79; p<0.001; r = 0.85; p<0.001) and delta R1 (r = 0.79; p<0.001; r = 0.69; p<0.01). Conclusion GDF-enhanced in vivo MRI is a powerful non-invasive imaging technique in mice allowing for reliable estimation of atherosclerotic plaque burden, monitoring of disease progression and regression in preclinical studies.